MY CHALLENGING ON QUIZIZZ: EFL LEARNERS’ PERCEPTIONS ON QUIZIZZ IN LITERAL READING - Ima Chusnul Chotimah; Dian Anik Cahyani (STKIP PGRI Jombang, 2021)
Over the years, the teaching and learning of English have changed from conventional chalk and talk methods to modern methods that involve various platforms such as Quizizz, which is free and easy to use. This study attempts to explores on EFL learners’ perceptions on Quizizz in Literal Reading. Using the case study approach, a total of 30 EFL learners were identified in this research. The results show that EFL learners’ Perceptions look highly upon Quizizz and its implementation in the classroom because it brings many benefits to the learners, including improvement in language proficiency and learning abilities. As a final result, EFL learners’ Perceptions toward E-Learning Quizizz in Literal Reading it can be concluded that 60.8% of respondents agreed, 26.8% stated strongly agree and 12, 4% disagreed related to the using of Quizizz in Literal Reading.